Designing for empowerment impact - The Agriculture, Nutrition, and Gender Linkages (ANGeL) project in Bangladesh - Ahmed, Akhter (International Food Policy Research Institute, 2019)
Presented by Akhter Ahmed (International Food Policy Research Institute), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.